Narrowing the definition of Networked Learning: A demarcation from the learner centred perspective - Brandtstedt, Lisa (Proceedings of the International Conference on Networked Learning, 2024)
This is a conceptual-philosophical paper and its intention is to address the issue of the definition of Networked Learning which is currently under discussion within the Networked Learning Editorial Community and revolves around the intellectual foundations on which the concept of NL rests. These intellectual foundations are according to some, myself included, overly inclusive and would benefit from some demarcation. This paper suggests such a demarcation through the dissociation of NL from the cognitive constructivist learner-centred perspective on education, which would define Networked Learning more clearly with respect to other adjacent research communities and educational concepts (e.g. Learning Sciences). The dissociation from learner-centrism is argued for on epistemological, pedagogical, and ideological grounds within the context of formal education, and a content-centred perspective is suggested in its stead.